The role of autologous stem cell transplantation in patients with nodal peripheral T‐cell lymphomas in first complete remission: Report from COMPLETE, a prospective, multicenter cohort study. Issue 9 (29th January 2019) - Park, Steven I.; Horwitz, Steven M.; Foss, Francine M.; Pinter‐Brown, Lauren C.; Carson, Kenneth R.; Rosen, Steven T.; Pro, Barbara; Hsi, Eric D.; Federico, Massimo; Gisselbrecht, Christian; Schwartz, Marc; Bellm, Lisa A.; et al.
Abstract : Background: The role of autologous stem cell transplantation (ASCT) in the first complete remission (CR1) of peripheral T‐cell lymphomas (PTCLs) is not well defined. This study analyzed the impact of ASCT on the clinical outcomes of patients with newly diagnosed PTCL in CR1. Methods: Patients with newly diagnosed, histologically confirmed, aggressive PTCL were prospectively enrolled into the Comprehensive Oncology Measures for Peripheral T‐Cell Lymphoma Treatment (COMPLETE) study, and those in CR1 were included in this analysis. Results: Two hundred thirteen patients with PTCL achieved CR1, and 119 patients with nodal PTCL, defined as anaplastic lymphoma kinase–negative anaplastic large cell lymphoma, angioimmunoblastic T‐cell lymphoma (AITL), or PTCL not otherwise specified, were identified. Eighty‐three patients did not undergo ASCT, whereas 36 underwent consolidative ASCT in CR1. At the median follow‐up of 2.8 years, the median overall survival was not reached for the entire cohort of patients who underwent ASCT, whereas it was 57.6 months for those not receiving ASCT ( P = .06). ASCT was associated with superior survival for patients with advanced‐stage disease or intermediate‐to‐high International Prognostic Index scores. ASCT significantly improved overall and progression‐free survival for patients with AITL but not for patients with other PTCL subtypes. In a multivariable analysis, ASCT was independently associated with improved survival (hazard ratio, 0.37; 95% confidence interval, 0.15‐0.89). Conclusions: This is the first large prospective cohort study directly comparing the survival outcomes of patients with nodal PTCL in CR1 with or without consolidative ASCT. ASCT may provide a benefit in specific clinical scenarios, but the broader applicability of this strategy should be determined in prospective, randomized trials. These results provide a platform for designing future studies of previously untreated PTCL. Abstract : This large prospective cohort study directly compares the survival outcomes of patients with nodal peripheral T‐cell lymphoma in first complete remission with or without consolidative autologous stem cell transplantation. Autologous stem cell transplantation is associated with superior survival for patients with advanced‐stage disease or an intermediate‐to‐high International Prognostic Index and with improved overall and progression‐free survival for patients with angioimmunoblastic T‐cell lymphoma.